Additive Manufacturing Technologies 2015
DOI: 10.1007/978-1-4939-2113-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Direct Digital Manufacturing

Abstract: Direct digital manufacturing (DDM) is a term that describes the usage of additive manufacturing technologies for production or manufacturing of end-use components. Although it may seem that DDM is a natural extension of rapid prototyping, in practice this is not usually the case. Many additional considerations and requirements come into play for production manufacturing that are not important for prototyping. In this chapter, we explore these considerations through an examination of several DDM examples, disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
443
1
28

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(474 citation statements)
references
References 1 publication
2
443
1
28
Order By: Relevance
“…If the material has a high specific heat capacity and high thermal conductivity, more heat initially must be added to soften the polymer. The benefit of this is that more heat can be distributed after deposition between the printed tracks to improve the polymer sintering process [ 31 ]. Having a high specific heat capacity and thermal conductivity is therefore beneficial to the FFF process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the material has a high specific heat capacity and high thermal conductivity, more heat initially must be added to soften the polymer. The benefit of this is that more heat can be distributed after deposition between the printed tracks to improve the polymer sintering process [ 31 ]. Having a high specific heat capacity and thermal conductivity is therefore beneficial to the FFF process.…”
Section: Methodsmentioning
confidence: 99%
“…FFF works best with polymers that are amorphous, despite their lower mechanical performance, as they have no distinct melting point and increasingly soften (lower viscosity) with increasing temperature. This means the polymer sintering process happens over a longer time when cooling down [ 31 ]. The polymer sintering process is related to material flow and the reptation time, which is the time required to create a fully welded, entangled interface.…”
Section: Methodsmentioning
confidence: 99%
“…The application of the multi-material printing technologies has been limited in the context of the aircraft industry. However, Gibson et al showed the possibility of printing a conductive wire sensor onto a turbine blade structure [35].…”
Section: Mixed Materialsmentioning
confidence: 99%
“…The high level of geometric freedom that additive manufacturing technologies allow [ 7 ] significantly increases possible design solutions. In this context, parametric design and optimization processes become very important [ 8 ].…”
Section: Introductionmentioning
confidence: 99%